2007
DOI: 10.1080/13546800600985557
|View full text |Cite
|
Sign up to set email alerts
|

Emotion perception and social skill over the course of psychosis: A comparison of individuals “at-risk” for psychosis and individuals with early and chronic schizophrenia spectrum illness

Abstract: Social skill deficits may be a vulnerability marker for schizophrenia, and it appears that the initial psychotic episode represents a critical point for the emergence of emotion perception deficits in schizophrenia spectrum illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
125
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 43 publications
13
125
0
4
Order By: Relevance
“…A previous study did not detect any differences between control individuals and a very small (n¼19) clinical high-risk sample. 3 The young people in our at-risk sample were seeking help and had significant disability. Their ability to identify emotions did not differ from the patient groups and was significantly worse than the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study did not detect any differences between control individuals and a very small (n¼19) clinical high-risk sample. 3 The young people in our at-risk sample were seeking help and had significant disability. Their ability to identify emotions did not differ from the patient groups and was significantly worse than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…After each stimulus, the participant makes a forced choice by selecting which of the six emotions is depicted. The score is the sum of the number of correct emotion identifications (0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) …”
mentioning
confidence: 99%
“…One important component of social cognition that has been extensively studied in schizophrenia patients is the ability to recognize emotions in the faces of others (Mandal et al 1998 ;Whittaker et al 2001 ;Edwards et al 2002 ;Hooker & Park, 2002 ;Bolte & Poustka, 2003 ;Kohler et al 2003 ;Schneider et al 2006 ;Pinkham et al 2007 ;PomarolClotet et al 2010). There are consistent findings of an impairment in facial emotion recognition (FER) in schizophrenia (for review see Kohler et al 2010), and these deficits have been shown to be associated with abnormal neural activity (Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…7 The fact that no differences were found between the ES and LS groups in most FAST domains may be explained by their similar scores in the assessment of some factors that may potentially affect functioning, such as psychotic symptoms (similar scores in BPRS) and educational attainment. Clinical and functioning improvements are not necessarily concurrent, and functioning impairment may persist in case of symptom remission.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, studies have found that psychosocial functioning impairment is not significantly different between patients with a first episode and those with multiple episodes, which suggests that an early and effective psychometric instrument should be used to assess psychosocial functioning in these patients. 1,7 Optimum care of individuals with SZ is heterogeneous, as it should include a personalized approach best fitted to relieve symptoms, restore functioning and prevent further illness progression. To improve treatment and maximize recovery, 2 studies should investigate how and if these psychopathological dimensions (symptoms and functioning) correlate.…”
Section: Introductionmentioning
confidence: 99%